Project Management Advances in the Field of Construction : A Review - Jain, Amit; Malviya, Pratiksha (International Journal of Scientific Research in Civil Engineering, 2019)
The improvement business accepts significant part in the economy of making countries. For example, in various making countries, critical advancement practices speak to around 80% of the total capital assets, 10 % of their GDP, and over portion of the wealth place assets into settled assets. In addition, the industry gives high business opportunity, undoubtedly next after agribusiness. Regardless of the improvement business' enormous responsibility to the economy of making countries and the fundamental part it plays in those countries progression, the execution of the business still stays all things considered low. As noticed, various endeavors in making countries encounter broad time and cost attacks, disregard to comprehend their normal favorable position or even totally finished and surrendered already or after their wrap up. Additionally, the change of the advancement business in making countries all things considered falls far behind from various endeavors in those countries and their accomplices in made nations. The advancement business in making countries fail to meet wants for governments, clients and society generally speaking.In this review paper we are presenting the past reseaches related to project management and advances done in project management tool.
Keywords: GDP; Primavera P6; C-sweetheart; MAS; Project Life Cycle; I.S. 7272